Occurrence of yttrium in the Zhijin phosphorus deposit in Guizhou Province, China - Chen Jiyan; Yang Ruidong; Zhang Jie; Chao Jinxing (Open Geosciences, 2022)
The Zhijin phosphorite (P)-bearing rare earth element (REE) deposit in Guizhou Province (China) hosts vast ore resources (P: 1.348 billion tonnes; REE: 1.44 Mt). Up to date, the Zhijin phosphorite resource has not been exploited because of the uncertain occurrence of the associated REEs, which hampers mineral processing and extraction. In this study, the structure, the valence state, and the coordination position of Y in the REE-yttrium-rich bioclastic samples from Zhijin were revealed by means of synchrotron radiation X-ray absorption fine structure analysis. The results show that the Y occurs as Y(iii) in the samples, and that the form of Y is different from the Y2O3 form in standard xenotime samples. Yttrium in the samples was in a complex coordination position without Y–O–Y bonding, and the Y–O bond lengths range widely without clear patterns. We suggest that Y in the samples is surrounded by organic or macro-molecular compounds, rather than in inorganic ones. Thus, Y in collophanite is unlikely to be in the form of isomorphism.